RASIO KEMANDIRIAN DAERAH DAN POTENSI PENDAPATAN ASLI DAERAH DI KABUPATEN LOMBOK TIMUR - OKKY AFRIWAN; AGUS MARJAN SAPUTRA; LALU MUH. KABUL (GANEC SWARA, 2023)
In the context of fiscal decentralization, regions are required to increase independence. The purpose of this study was to analyze the ratio of regional independence and potential local revenue (PAD) in East Lombok Regency. The method used in this study is a mixed method, namely quantitative and qualitative. From the research results it was found that the East Lombok Regional Independence Ratio value in the 2018-2022 period ranged from 11.321 percent to 14.737 percent or was in the range of 0-25%; meaning that it belongs to the category of very low financial ability with an instructive relationship pattern. Meanwhile, various PAD that have the potential to be developed for increasing PAD towards regional independence, namely regional taxes, regional levies, regional wealth management results, and other income.